2019
DOI: 10.1002/jlcr.3803
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and preliminary bioevaluation studies of 68Ga‐NOTA‐rituximab fragments as radioimmunoscintigraphic agents for non‐Hodgkin lymphoma

Abstract: Rituximab is used for the treatment of non‐Hodgkin lymphoma (NHL). This study focuses on development of 68Ga‐labeled rituximab fragments, (68Ga‐NOTA‐F (ab′)‐rituximab and 68Ga‐NOTA‐F (ab′)2‐rituximab, as PET‐imaging agents for NHL. Rituximab was digested with immobilized pepsin and papain to yield F (ab′)2 and Fab fragments respectively that were characterized by size exclusion HPLC (SE‐HPLC) and SDS‐PAGE. They were conjugated with p‐SCN‐Bn‐NOTA, labeled with 68Ga and characterized by SE‐HPLC. Intact rituximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Moreover, both 64 Cu-NOTA-F(ab9) 2 -obinutuzumab in CCL-155 tumors and 64 Cu-NOTA-F(ab9) 2 -IgG in Ramos tumors showed significantly lower tumor contrast at 48 h after injection (respectively: T/B 5 1.5 6 0.5 and 1.1 6 0.3; T/M 5 7.9 6 4.0 and 4.6 6 2.4). Although 68 Ga-labeled F(ab) and F(ab9) 2 for rituximab have previously been developed, they were evaluated at only the cellular level (21). Therefore, our study confirmed that 64 Cu-labeled F(ab9) 2 -obinutuzumab is promising for evaluating the differential CD20 expression of lymphoma noninvasively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, both 64 Cu-NOTA-F(ab9) 2 -obinutuzumab in CCL-155 tumors and 64 Cu-NOTA-F(ab9) 2 -IgG in Ramos tumors showed significantly lower tumor contrast at 48 h after injection (respectively: T/B 5 1.5 6 0.5 and 1.1 6 0.3; T/M 5 7.9 6 4.0 and 4.6 6 2.4). Although 68 Ga-labeled F(ab) and F(ab9) 2 for rituximab have previously been developed, they were evaluated at only the cellular level (21). Therefore, our study confirmed that 64 Cu-labeled F(ab9) 2 -obinutuzumab is promising for evaluating the differential CD20 expression of lymphoma noninvasively.…”
Section: Discussionsupporting
confidence: 78%
“…Although antibody fragments can significantly enhance blood clearance and tumor contrast, these small tracers typically undergo rapid renal filtration and elimination (16). Radiolabeled agents of similar or smaller size would also have high renal uptake (21). These lead to high kidney accumulation and may induce nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For collision breast tumors of BC and NHL, the use of some specially formulated contrast agents may be helpful for differentiating. The potential of 68Ga-NOTA-F (ab′)2-rituximab and 68Ga-NOTA-F (ab′)-rituximab as PET imaging agents for NHL has been reported [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most popular procedure for determining the number of DOTA molecules conjugated to the antibody is the colorimetric method measuring the absorbance of a solution containing complexes of metal ions (such as Cu 2+ , Pb 2+ , Y 3+ , or Tb 3+ ) and Arsenazo­(III). It measures the number of mAb-bound metal chelator molecules available for metal binding. , Those methods bring some benefits like simplicity and relatively fast determination. However, the main limitation is the low sensitivity in the micromolar range, so the accuracy of the DOTA/mAb ratio is very low.…”
Section: Measurement Of the Number Of The Chelators Per Monoclonal An...mentioning
confidence: 99%
“…A few literature reports cover the use of rats in research on radiolabeled Rituximab, , but the overwhelming majority of the reports relate to the murine model, Table . The latter model encompasses both healthy ,,,, and immunodeficient mouse strain, that is, NOD/SCID and Nude. ,,, Transplantable xenograft models were subcutaneously grafted with RAJI, DAUDI, or RAMOS cells from existing cell lines, not from the primary tumor origin (patient-derived). The advantage of this approach was undoubtedly rapid result, relative simplicity, high yield, usefulness as first step investigation, determining in vivo proof-of-concept from in vitro findings like immunoreactivity and examining the efficacy of radiotherapeutics on human tumor cells.…”
Section: Comparison Of In Vivo Studiesmentioning
confidence: 99%